Glycopeptide microarray for autoantibody detection in cancer. (August 2011) - Reis, Celso A; Campos, Diana; Osório, Hugo; Santos, Lúcio Lara
Evaluation of: Pedersen JW, Blixt O, Bennett EP et al. Seromic profiling of colorectal cancer patients with novel glycopeptide microarray. Int. J. Cancer 128(8), 1860–1871 (2011). Autoantibodies to cancer-associated antigens hold promise as sensitive biomarkers for cancer detection. Based on this hypothesis, and knowing that O -glycans on proteins constitute a source of possible epitopes recognized by autoantibodies, Pedersen and colleagues have generated a glycopeptide array displaying a comprehensive library of glycopeptides and glycoproteins derived from human mucins. The profiling of sera immunoreactivity of colon cancer patients allowed the identification of cancer-associated autoantibodies to various mucin (MUC)1 and MUC4 glycopeptides carrying aberrant glycosylation. This article provides evidence for the value of glycopeptides displaying cancer-associated glycans in diagnostic applications, and opens new avenues for the expansion to other protein glycoforms, as well as to further applications of such a microarray strategy for other post-translational modifications of proteins in the search for cancer biomarker.